Femoral Version, Neck-Shaft Angle, and Acetabular Anteversion in Chinese Han Population: A Retrospective Analysis of 466 Healthy Adults - Jiang, Nan (Medicine (Baltimore), 2015)
Anatomic data regarding femoral version, neck-shaft angle, and acetabular anteversion are still limited in Chinese Han adult population. The aim of this study was to investigate the effects of age, sex, and body laterality on the 3 important anatomic indicators in Chinese Han healthy adults. Measurements were performed independently by 3 experienced observers using the picture archiving and communication system (PACS) in healthy adults who had received imaging tests of the femur and acetabulum between January 2009 and October 2014. Relevant data were measured and analyzed. A total of 466 adults (353 males and 113 females) were included. The mean femoral version, neck-shaft angle, and acetabular anteversion for all were 10.62, 133.02, and18.79, respectively. Age-based analysis showed that adults younger than 60 years had a significantly higher neck-shaft angle (P < 0.001) but a significantly lower acetabular anteversion (P < 0.001) than those older than 60 years. Sex-based analysis revealed that females had significantly higher values of femoral version (P < 0.001) and acetabular anteversion (P < 0.001) than males. Laterality-based analysis found the left side had a significantly lower acetabular anteversion (P < 0.001) than the right side. Outcomes of multiple linear regression analysis indicated that femoral version may be associated with sex (P < 0.001) but not age (P = 0.076) or laterality (P = 0.430), neck-shaft angle may be associated with age (P < 0.001) but not sex (P = 0.378) or laterality (P = 0.233), and acetabular anteversion may be associated with age (P < 0.001) and sex (P < 0.001) but not laterality (P = 0.060). In this representative Chinese cohort, neck-shaft angle may decrease, whereas acetabular anteversion may increase with age, females may have higher values of femoral version and acetabular anteversion than males, and the right body side may have a higher value of acetabular anteversion than the left side.